Urban nitrous-oxide fluxes measured using the eddy-covariance technique in Helsinki, Finland - Jarvi, Leena; Nordbo, Annika; Rannik, Ullar; Haapanala, Sami; Riikonen, Anu; Mammarella, Ivan; Pihlatie, Mari; Vesala, Timo (Finnish Environment Institute, 2016)
Peer reviewed